Effect of Banbar Extract on some Male Reproductive Organs of the Swiss Mice - Hanady S. Abed Al-sahin (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2005)
This study has been carried out on the male Swiss mice to define he effect of banbar seed extract on the testis. epididymis and its side effects on spermatogenesis . The results showed a significant decrease (p<0.05) in the sertoli cells ,sperm numbers, secondary spermatocytes and sperm concentration. Histopathological study in testis showed necrosis, degeneration, detachement of germ cells ,vasodilatation and appearance of spermiophygus in the lumen of tubules. On the epididymus, there was hypoplasia, detachment of epithelium from basement membrane and macrophages in high percentages.